Measuring concentrations of a dye in the hemolymph of a marine amphipod: Development of a protocol for exposure assessment - dos Santos, Amanda; Vannuci-Silva, Monizze; Vendemiatti, Josiane A. de Souza; Artal, Mariana Coletty; Silva, Bianca Ferreira da [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Umbuzeiro, Gisela de Aragão (Elsevier, 2022)
The increasing pollution of aquatic environments due to old and emerging contaminants requires the development of integrative methods for exposure assessment. Internal concentrations are a reliable way to estimate total exposure of contaminants originated from different routes (water, sediment, and food). We developed a protocol to evaluate the concentration of a dye, C.I. Disperse Red 1, in the hemolymph of Parhyale hawaiensis, a marine amphipod. LOD and LOQ were satisfactory to detect the dye in all hemolymph samples. The concentration detected in the hemolymph varied related to exposure time and dye concentration (0.003 to 0.086 μg mL−1). Polynomial regression model was the best fit. The protocol was reliable to detect and quantify dye exposure in marine amphipods and can be considered for future assessments of estuarine and marine regions under the influence of dye processing plants. The method possibly can be easily adapted to other amphipods and other azo dyes.
Keywords: C.I. Disperse Red 1; Crustacean; Nitrophenylazo dye; Parhyale hawaiensis; Uptake